2013
DOI: 10.2489/jswc.68.5.392
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of soil and water conservation practices on potato yield in northwestern New Brunswick, Canada

Abstract: We investigated the effects of soil and water conservation practices on mean and variance of potato (Solanum tuberosum L.) yield across 267 fields in northwestern New Brunswick, Canada, from 1988 to 2010. A stochastic production function method was used to account for seven soil and water conservation practices in addition to farm inputs, potato varieties, technological change, site characteristics, and seasonal climate effects. Overall, soil and water conservation structures had mixed effects on potato yield.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…Similar potato yield decreases, as a result of delaying plowing to spring, were seen in other studies (Carter & Sanderson, ; Carter et al., , , ; Holmstrom et al., ; Lynch et al., ) although Ochuodho et al. () and DeHaan et al. () reported higher yield under spring plowing with lower variance compared with fall plowing.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Similar potato yield decreases, as a result of delaying plowing to spring, were seen in other studies (Carter & Sanderson, ; Carter et al., , , ; Holmstrom et al., ; Lynch et al., ) although Ochuodho et al. () and DeHaan et al. () reported higher yield under spring plowing with lower variance compared with fall plowing.…”
Section: Resultssupporting
confidence: 76%
“…In PEI, potato is typically grown in rotation with cereal grains (e.g., barley, Hordeum vulgare L.) underseeded with forages (e.g., grass-legume mixtures), which are plowed down in the autumn of the second season as a green manure. One major drawback of fall plowing of forage includes increased wind and water erosion of soil by as much as 8 Mg ha −1 yr −1 (Edwards et al, 1998), which has negative impacts on soil quality and potato yield (DeHaan et al, 1999;Ochuodho et al, 2013). Holmstrom, DeHaan, Sanderson, and MacLeod (1999) found that soil erosion is incredibly costly to PEI producers, amounting to roughly $5 million annually.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, every 0.1 cmol kg -1 increase in CEC and each percentage increase in soil sand content increased potato yield by 1.5 and 0.2%, respectively. Overall, in the Step 2 regression analysis, most relationships tended to be as expected and were consistent with the findings of previous studies that showed how increasing farm inputs tends to lead to higher potato yield (Cabas et al, 2010;Ochuodho et al, 2013). However, the slightly negative effect of precipitation on potato yield was likely to be a reflection of the fact that there were several abnormally wet years (especially 2011) during the study period (van Loon, 1981;Bourke, 1989).…”
Section: Potato Yield Analysissupporting
confidence: 88%
“…In response to the declining soil quality, farmers in this area have adopted various BMPs, such as diversion terraces, crop rotation, and conservation tillage. The biophysical and hydrological effects of many BMPs have been extensively studied in this watershed (e.g., Rees et al, 2002;Yang et al, 2009;Ochuodho et al, 2013).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation